Molecular cloning of the bombesin/gastrin-releasing peptide receptor from Swiss 3T3 cells. - Battey, J F (1991)
The mammalian bombesin-like peptides gastrin-releasing peptide (GRP) and neuromedin B regulate numerous and varied cell physiologic processes in various cell types and have also been implicated as autocrine growth factors influencing the pathogenesis and progression of human small cell lung carcinomas. We report here the molecular characterization of the bombesin/GRP receptor. Structural analysis of cDNA clones isolated from Swiss 3T3 murine embryonal fibroblasts shows that the GRP receptor is a member of the guanine nucleotide binding protein-coupled receptor superfamily with seven predicted hydrophobic transmembrane domains. In vitro transcripts from cloned cDNA templates encompassing the predicted protein coding domain, when injected into Xenopus oocytes, resulted in expression of functional GRP receptors. The predicted amino acid sequence of the open reading frame in cDNA clones matches the amino-terminal sequence as well as the sequence of four tryptic fragments isolated from the purified protein. Expression of the GRP receptor cDNA in model systems potentially provides a powerful assay for the development of subtype-specific receptor antagonists that may prove to be of therapeutic importance in human small cell lung carcinoma.